Avaliação da eficiência do tratamento de esgoto doméstico pelo teste do micronúcleo em Oreochromis niloticus (Cichlidae) - Del-Guercio, Anita Martins Fontes [UNESP]; Christofoletti, Cintya Aparecida [UNESP]; Fontanetti, Carmem Silvia [UNESP] (FapUNIFESP (SciELO), 2017)
This study aimed at evaluating the efficiency in the domestic wastewater treatment from a city of Sao Paulo State (Brazil), by micronuclei and nuclear abnormalities analysis in erythrocytes of tilapias exposed to raw and treated wastewater. Two samples were collected. Three aquariums of 20 L, with five fish each, were used in the bioassays. In the first, the animals were exposed to the artesian water (negative control); in the second, to the diluted raw wastewater; and in the third, to after wastewater treatment. After the exposure time (72 h), the blood was collected for preparing the smear slides. The results showed genotoxic and mutagenic effects of the raw wastewater in both samples, showing that the process used was efficient to minimize these effects.
Evaluation of the domestic wastewater treatment efficiency by micronucleus test on Oreochromis niloticus (Cichlidae)
Keywords: Domestic wastewater; Genotoxicity; Mutagenicity; Tilapia; Upflow anaerobic sludge Blanket